Governing health data across changing contexts: A focus group study of citizen's views in England, Iceland, and Sweden. (December 2021) - Shah, N.; Viberg Johansson, J.; Haraldsdóttir, E.; Bentzen, H.B.; Coy, S.; Mascalzoni, D.; Jónsdóttir, G.A.; Kaye, J.
Highlights: Summary Table What was already known on the topic? Linking health data from different contexts may help better understand health outcomes. Public dialogue is needed to address the data trust deficit on secondary uses of data. What this study added to our knowledge? Improving public awareness about health data flows and their data rights is needed. Health data sharing preferences depend on purposes and reciprocity of benefits. Providing data subjects more detail and data sharing options would improve choices. Abstract: Background: The governance structures associated with health data are evolving in response to advances in digital technologies that enable new ways of capturing, using, and sharing different types of data. Increasingly, health data moves between different contexts such as from healthcare to research, or to commerce and marketing. Crossing these contextual boundaries has the potential to violate societal expectations about the appropriate use of health data and diminish public trust. Understanding citizens' views on the acceptability of and preferences for data use in different contexts is essential for developing information governance policies in these new contexts. Methods: Focus group design presenting data sharing scenarios in England, Iceland, and Sweden. Results: Seventy-one participants were recruited. Participants supported the need for data to help understand the observable world, improve medical research, the quality of public services, and to benefit society. However, participants consistently identified the lack of information, transparency and control as barriers to trusting organisations to use data in a way that they considered appropriate. There was considerable support for fair and transparent data sharing practices where all parties benefitted. Conclusion: Data governance policy should involve all stakeholders' perspectives on an ongoing basis, to inform and implement changes to health data sharing practices that accord with stakeholder views. The Findings showed that (1) data should be used for ethical purposes even when there was commercial interest; (2) data subjects and/or public institutions that provide and share data should also receive benefits from the sharing of data; (3) third parties use of data requires greater transparency and accountability than currently exists, (4) there should be greater information provided to empower data subjects.